Influence of group size on mice behaviour in standard tests - Avimova, Kseniya P.; Sandakov, Dmitry B. (Experimental Biology and Biotechnology, 2023)
The influence of housing conditions (single, pair or group) on mice behaviour in standard tests (open field test, holeboard test, tail suspension test and elevated X-maze test) was studied. Group housing lead to increased time of grooming and freezing episodes in open field test. In hole-board test, group-housed mice demonstrated the least efficiency of exploratory activity. Single- and pair-housed mice were spending more time in closed arms of elevated X-maze (compared with open arms), and group-housed mice didn’t show the preference of closed arms. After 30 days under different experimental conditions, the least skin damage level was observed in pair-housed mice. Meanwhile, the dynamics of weight gain was similar in all animals.
Keywords: laboratory mice; conditions for housing of animals; single housing; group housing; behavioural tests; open field test; hole-board test; tail suspension test; elevated X-maze test; social stress